Bioativos em formulações cosméticas para rejuvenescimento cutâneo - Costa, Danielly da Silva (Brasil, 2024)
The reviewed studies on hyaluronic acid, vitamin A, and vitamin C demonstrate their efficacy and versatility in skincare. Hyaluronic acid, known for its moisturizing properties, works on moisture retention, providing deep hydration and helping to reduce the appearance of fine lines and wrinkles. Additionally, hyaluronic acid stimulates collagen production, promoting skin firmness and elasticity. Vitamin A, in its active forms such as retinoids, has been shown to be effective in treating various dermatological conditions, including hyperpigmentation and signs of aging. Retinoids stimulate cell renewal, increase collagen production, and improve skin texture, providing a younger and healthier appearance. In turn, vitamin C stands out for its potent antioxidant action and its role in collagen synthesis. It protects the skin against damage caused by free radicals, reduces hyperpigmentation, and enhances the overall appearance of the skin, promoting a brighter and more uniform appearance. Although these ingredients offer a variety of benefits for the skin, it is important to consider their possible side effects, such as irritation and sensitivity, especially during the initial weeks of use. Additionally, it is essential to choose appropriate formulations and follow usage and storage recommendations to achieve the best results and minimize any potential risk. In summary, hyaluronic acid, vitamin A, and vitamin C represent valuable options for promoting skin health and beauty, offering a comprehensive and effective approach to dermatological care.